WORKING AS VENDORS AS A PROFESSION CHOSEN BY PEOPLE WITH LIMITED CAPITALS IN TOURISM SECTOR IN BALI - Ary Widiastini, Ni Made (E-Journal of Cultural Studies; Volume 7, Number 1, February 2014)
This study was intended to present the matters pertaining to the attempts made by the vendors ‘pedagang acung’ to keep being independent in tourism sector in Bali. As working people with extremely limited capitals, the principle of giving priority to safety is applicable to them. They sell souvenirs with limited capitals obtained from various souvenir entrepreneurs coming from different parts of Bali. The risk of suffering from loss has never caused them to find any difficulty. This qualitative study was conducted in the paradigm of cultural studies. The data were presented and interpreted in the form of narrative texts which are thick descriptive in nature.   The result of the study showed that working as vendors was still a profession which contributed to the decrease in unemployment in an area. This is in line with the concept of poststructuralism that people are basically referred to as homo faber, namely, the working creature, meaning that working is highly important to man. This means that employment does not only give the opportunity to generate income but also importantly means that employment is a personal identity. As a consequence, if working is different from not working or being jobless, then such a choice does not only lead to an opposing binary but also to a hierarchical social division and a structured social gap between those who are employed and those who are not. They all positively contribute to themselves, environment, entrepreneurs, and the local government.
Keywords: ‘pedangang acung’, profession, limited capital, tourism sector.